10-year follow-up after standardised treatment for Achilles tendinopathy. Issue 1 (4th October 2018) - Johannsen, Finn; Jensen, Signe; Wetke, Eva
Abstract : Background: Achilles tendinopathy is a common and often long-lasting injury. We present a 10-year follow-up on a pragmatic study on Achilles tendinopathy treated with controlled exercises supplemented with corticosteroid injections if necessary in order to continue training. Methods: All patients who completed the original study (n=93) were invited for a 10-year follow-up. 83% participated. Patients were evaluated with ultrasound scanning (n=58) and with a questionnaire (n=77) using the same outcome measures as in the primary study. The 10-year overall outcome on a 4-point scale (excellent, good, fair, poor), other treatments and adverse event and present activity level were recorded. Results: Excellent outcome was reported in 63% and good outcome in 27%. 76% reported an activity level at 75%–100% of preinjury level. The average Victorian Institute of Sports Assessment-Achilles score for all patients was 84 (SD 19). 16% had surgery. Three ruptures occurred 5–8 years after the primary study. The improvement from entry to 6 months in the primary study was maintained until 10-year follow-up. Insertional tendinopathy did not differ from mid-substance tendinopathy in any outcome measure (short term and long term). We encountered no prognostic markers on ultrasound for the long-term outcome; however, present heterogeneity and increased flow resemble present pain. Thickened tendons seem to maintain their thickness despite improvement of symptoms. Conclusion: One to two corticosteroid injections are a safe and effective supplement to controlled exercises in the treatment of Achilles tendon pain with no signs of deterioration in the very long term. Mid-substance and insertional tendinopathies benefit equally from this treatment.